Novel Separate Confinement Heterostructure Design for Long-Wavelength Lasers - Yong, Y. S.; Wong, H. Y.; Yow, H. K. (IEEE, 2011)
A novel nonsymmetrical separate confinement heterostructure (SCH) design for the long-wavelength multiple-quantum-well lasers is proposed. It is shown to be capable of reducing electron leakage and minimizing optical wave overlapping with the p-side SCH. As a result, significant improved output power and slope efficiency performance with respect to those of the laser structure with conventional SCH design had been observed.